Cadbury Committee : a history - Spira, Laura F. (OUP, 2013)
"The Committee on the Financial Aspects of Corporate Governance, better known as the Cadbury Committee, was set up in May 1991 to address the concerns increasingly voiced at that time about how UK companies dealt with financial reporting and accountability and the wider implications of this. The Committee was sponsored by the London Stock Exchange, the Financial Reporting Council, and the accountancy profession, and published its final report and recommendations in December 1992. Central to these was a Code of Best Practice and the requirement for companies to comply or to explain to their shareholders why they had not done so. The recommendations and the Code provided the foundation for the current system of corporate governance in the UK and have proved very influential in corporate governance developments throughout the world. While academics and practitioners have explored and discussed the developments in corporate governance since 1992, little attention has been paid to the processes of code and policy development. This book explores the origins of the Committee, provides rich insights in to the way in which it worked, and documents the reaction to the publication of the Committee's report."--Publisher's description.